2014
DOI: 10.3389/fpls.2014.00590
|View full text |Cite
|
Sign up to set email alerts
|

Have plants evolved to self-immolate?

Abstract: By definition fire prone ecosystems have highly combustible plants, leading to the hypothesis, first formally stated by Mutch in 1970, that community flammability is the product of natural selection of flammable traits. However, proving the “Mutch hypothesis” has presented an enormous challenge for fire ecologists given the difficulty in establishing cause and effect between landscape fire and flammable plant traits. Individual plant traits (such as leaf moisture content, retention of dead branches and foliage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
1
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 114 publications
2
76
1
17
Order By: Relevance
“…Interestingly, the most fire-adapted indigenous species burned here, Mānuka, was not the most flammable of the indigenous species. Although our study was not designed to test their hypothesis, these findings support Bowman et al (2014) as we demonstrate high levels of flammability in species from communities that are rarely burnt. High shoot-level flammability was also recently reported for species that occur in the fire-free forest biome in South Africa (Calitz et al 2015).…”
Section: Flammability Of New Zealand Trees and Shrubssupporting
confidence: 69%
See 3 more Smart Citations
“…Interestingly, the most fire-adapted indigenous species burned here, Mānuka, was not the most flammable of the indigenous species. Although our study was not designed to test their hypothesis, these findings support Bowman et al (2014) as we demonstrate high levels of flammability in species from communities that are rarely burnt. High shoot-level flammability was also recently reported for species that occur in the fire-free forest biome in South Africa (Calitz et al 2015).…”
Section: Flammability Of New Zealand Trees and Shrubssupporting
confidence: 69%
“…This is the case for some tree fern species and also Cabbage Tree (Cordyline australis). The retention of dead leaf material increases plant flammability (Bowman et al 2014), and preliminary tests found dead tree fern and Cabbage Tree fronds were more flammable than the corresponding live material. For such species the flammability of the dead material will likely be a more important driver of plant flammability than that of a live shoot, yet the present method only measures this where dead material is part of a terminal shoot section.…”
Section: Suitability Of the Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike warm temperate rainforests, monsoon rainforest and tropical savanna are thus likely alternative stable states driven by fire . There is ongoing debate about the adaptive significance of plant traits linked to flammability (Bradshaw et al 2011;Keeley et al 2011;Bowman et al 2014). Mason et al (2016;this issue) explore this proposition in common native woody and herbaceous species of New Zealand, where fire has not been a strong selection pressure.…”
Section: Understanding and Characterising Fire Regimesmentioning
confidence: 99%